Color me honest! Time pressure and (dis)honest behavior - Hausladen, Carina I.; Nikolaychuk, Olexandr (Frontiers in Behavioral Economics, 2024)
We introduce three modifications to the die-in-a-cup paradigm to gain novel insights into dishonest behavior under time pressure. The regular die is substituted with a custom one that has a distinct color on each side as a way of manipulating familiarity with the decision situation. The cup is substituted with a 'dice tower' to control the randomization process. Alongside outcome data, we capture mouse cursor trajectories. Results from our preregistered laboratory experiment involving 229 subjects suggest that time pressure increases dishonesty only when the regular die is used. Mouse tracking analysis suggests that it takes more effort to be honest than to lie outright and that partial lying is most difficult.